Transcranial Direct Current Stimulation Reduces Negative Affect but Not Cigarette Craving in Overnight Abstinent Smokers - Xu, Jiansong; Fregni, Felipe; Brody, Arthur L.; Rahman, Ardeshir S. (Frontiers in Psychiatry, 2013)
Transcranial direct current stimulation (tDCS) can enhance cognitive control functions including attention and top-down regulation over negative affect and substance craving in both healthy and clinical populations, including early abstinent (∼1.5 h) smokers. The aim of this study was to assess whether tDCS modulates negative affect, cigarette craving, and attention of overnight abstinent tobacco dependent smokers. In this study, 24 smokers received a real and a sham session of tDCS after overnight abstinence from smoking on two different days. We applied anode to the left dorsolateral prefrontal cortex and cathode to the right supra-orbital area for 20 min with a current of 2.0 mA. We used self-report questionnaires Profile of Mood States (POMS) to assess negative affect and Urge to Smoke (UTS) Scale to assess craving for cigarette smoking, and a computerized visual target identification task to assess attention immediately before and after each tDCS. Smokers reported significantly greater reductions in POMS scores of total mood disturbance and scores of tension–anxiety, depression–dejection, and confusion–bewilderment subscales after real relative to sham tDCS. Furthermore, this reduction in negative affect positively correlated with the level of nicotine dependence as assessed by Fagerström scale. However, reductions in cigarette craving after real vs. sham tDCS did not differ, nor were there differences in reaction time or hit rate change on the visual task. Smokers did not report significant side effects of tDCS. This study demonstrates the safety of tDCS and its promising effect in ameliorating negative affect in overnight abstinent smokers. Its efficacy in treating tobacco dependence deserves further investigation.